Coffee Warehouse Receipt System at the MAI Independent Producer Cooperative: Implementation and Problems - Innike Abdillah Fahmi; Sisvaberti Afriyatna; Mustopa Marli Batubara; Rafeah Abubakar; Nia Rahmantia (Journal of Global Sustainable Agriculture, 2024)
Delaying sales in coffee marketing using the Warehouse Receipt System (WRS) scheme is carried out to avoid losses from selling coffee at low prices in Pagar Alam City. The implementation of WRS has been carried out at the MAI Mandiri Producer Cooperative since 2020, but still encountering obstacles. This research aims to determine the problems faced by the MAI Mandiri Producer Cooperative in implementing this WRS scheme and efforts to overcome these problems. The data collection method was in-depth interviews with informants at the Mandiri MAI Producer Cooperative and the data was analyzed using the Miles and Huberman Interaction Models. The research results show that the implementation of the WRS scheme has a clear flow, complies with the rules, running well and shortens the marketing chain. Meanwhile, the problems faced by the MAI Mandiri Producer Cooperative in implementing the WRS scheme are 1) there are still very few cooperative members participating in the WRS scheme, 2) there is still a lack of wooden pallets in the warehouse, 3) the upper limit (ceiling) of financing from banks is considered to be still small.